Biochar-Mediated Degradation of Roxarsone by Shewanella oneidensis MR-1 - Wengang, Li; Fang, Chen; Rong, Zhong; Cuihong, Chen (Frontiers in Microbiology, 2022)
It is widely believed that biochar plays an essential role in sequestrating pollutants. The impacts of biochar on microbial growth, and consequently on the environmental fate of pollutants, however, remains poorly understood. In this study, wheat-straw-derived biochar was used to investigate how biochar amendment affected Shewanella oneidensis MR-1 growth and roxarsone transformation in water under anaerobic conditions. Three biochar with different physicochemical properties were used to mediate the roxarsone degradation. The results showed that the degradation rate of roxarsone could be accelerated by the increase of biochar pyrolysis temperature. From the characterization of biochar, the total specific surface area, micropore surface area and micropore volume of biochar increase, but the average pore diameter decreases as the pyrolysis temperature increases. Through infrared spectroscopy analysis, it was found that as the pyrolysis temperature increases, the degree of condensation of biochar increases, thereby increasing the pollutant removal rate. From the changes of the relative concentration of MR-1 and its secreted extracellular polymer content, the growth promotion ability of biochar also increases as the pyrolysis temperature increases. These results suggest that wheat-straw-derived biochar may be an important agent for activating microbial growth and can be used to accelerate the transformation of roxarsone, which could be a novel strategy for roxarsone remediation.